PENGARUH ASIMETRI INFORMASI, SISTEM PENGENDALIAN INTERN, DAN KESESUAIAN KOMPENSASI TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI (STUDI EMPIRIS PADA BANK SWASTA DI KOTA PEKANBARU) - Frilia, Figna; Agusti, Restu; Savitri, Enni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this research was to examine the influence of information asymmetry Effect, Internal Controls, and Conformity Compensation Against the tendency of accounting fraud (Empirical Study on Private Bank in the city of Pekanbaru). The population in this research is the banking companies in the city of Pekanbaru in the period 2014 to the characteristics of banks that have not yet incoming the stock exchange. The sampling method in this research using the census method that looked at all objects studied by administering questionnaires as many as 3 people for each bank, assuming 1 for the marketing of credit, 1 for the internal control division, and 1 for staff / employees of the accounting division. Stastical methods used to test the research hypothesis is multiple regression using SPSS 17 software. The results of this research shows that information asymmetry has significant effect on tendency of accounting fraud. Internal Control System has not significant effect on tendency of accounting fraud. Conformity compensation has significant effect on tendency of accounting fraud.Keywords: asymmetry of information, internal control, conformity compensation, the tendency of accounting fraud